Identification of potential inhibitors of casein kinase 2 alpha of Plasmodium falciparum with potent in vitro activity - Tomaz, Kaira C.P. (2023)
Funding Information: The authors are incredibly grateful to Brazilian funding agencies Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), CNPq, CAPES, Fundação de Apoio à Pesquisa do Estado de Goiás (FAPEG), and to the Swedish Research Council (grants 2016–05627 and 2021–03667). K.C.P.T. thanks FAPESP (grants 2018/05926–2, and 2019/17062–5). FAPESP funded T.A.T. (2019/27626-3), J.V.B.B. (2019/21854-4), K.B.M. and R.M.C. (2014/50897-0), V.M.A. (2022/00743-2), G.C.C. (2015/20774-6), and F.T.M.C. (grants 2017/18611–7 and 2018/07007–4). L.C.S.A. was funded by CNPq (162117/2018– 3). E.B. was supported by FAPESP (2015/03553-6 and 2018/07007–4) and CAPES (88887.304810/2018–00). J.V.B.B. and J.T.M.F. were supported by CAPES (Finance Code 001). C.H.A. and M.M. thanks FAPEG (grants 20171026700006 and 202010267000272). C.H.A. thanks the “L'Oréal-UNESCO-ABC Para Mulheres na Ciência” and “L’Oréal-UNESCO International Rising Talents” for the awards and fellowships received, which partially funded this work. C.H.A. and F.T.M.C. are CNPq research fellows. We are thankful to Liam B. King for his critical review of the report. Publisher Copyright: © 2023 American Society for Microbiology. All Rights Reserved.